Structural equation modelling: validation of career readiness model using psychological constructs - Norazwa Yeop Kamarudin; Azlina Mohd Kosnin; Lina Handayani; Che Rozid Mamat (International Journal of Evaluation and Research in Education (IJERE), 2024)
The career readiness model is needed as a reference source for relevant parties, especially universities, to implement various career development and interventions initiatives. This study was conducted to assess the reliability and validity of personality, career efficacy, career readiness skills along with indicators using Partial Least Squares Structural Equation Modeling in forming a career readiness model. Results show that each construct achieved good reliability and validity through composite reliability (CR) readings recorded between 0.78 and 0.92 to measure internal consistency reliability, while convergent validity through average variance extracted (AVE) readings exceeded 0.5. The construct of this model had also achieved discriminant validity through the recorded readings of cross loading, Fornell-Larcker and HTMT confidence intervals which did not contain the value of 1. The findings also indicate that career efficacy and career readiness skills are accurate and relevant constructs for developing a career readiness model.